Training in Formative Assessment and Use of Mobile Applications for High School Teachers as a Community Service Activity of the Department of Medical Education, Faculty of Medicine, Universitas Hasanuddin - Asty Amalia Nurhadi; Sri Asriyani; Bau Dilam Ardyansyah; Irwin Aras; Budu (Future Science)
The digital revolution had transformed human life in many ways, including the way people learn. It affected students who are very dependent on mobile devices, social media, and mobile applications. These transformations demanded teachers to also transform. Teachers needed to embrace the technology and integrate it into their learning strategies. The Department of Medical Education of the Faculty of Medicine of Universitas Hasanuddin (FMUH) received a grant for a community service project from the faculty. This study describes training aimed at equipping high school teachers with the capability of using several mobile applications, including Google Forms, Quizizz, and Anki flashcards. The FMUH yearly intake was almost 300 students per year which were mostly high school fresh graduates in Indonesia. As the teachers of our future students, we considered the need for technology use in promoting teachers’ competence. Therefore, as our community service project, we held a one-day training for high school teachers which focused on the use of various mobile applications in formative assessment. At the end of our training, we elicited our participants’ evaluation using a Likert-scale questionnaire and open-ended questions. The responses were analyzed using statistical and descriptive analysis. This training involved 79 teachers and the evaluation form was filled out by 55 participants. The analysis showed that all respondents agreed that the training was able to increase their competence in using mobile applications for formative assessment. They pointed out the importance of this training in increasing the quality of education. This training was considered very useful in increasing high school teachers’ competence in formative assessment as well as in digital learning. This type of training was proposed to be frequently conducted.